Wear mechanisms map of CNT-Al nano-composite - Abdullahi, U.; Maleque, Md. Abdul; Nirmal, U. (Elsevier, 2013)
Carbon nanotube reinforced aluminium nano-composites were produced using powder metallurgy route with different weight percent of CNT into the Al matrix. The wear behaviour of pure aluminium (Al) and carbon nanotube reinforced aluminium (CNT-Al) nano-composite with different CNT content were studied with a pin-on-disc tribometer, sliding against AISI52100 steel disc. Experiments were conducted using different sliding velocities of 0.5, 0.65 and 0.79 m/s and a normal load of 5.5, 7.2 and 10 N. From the wear map it is observed that, during dry sliding wear an increase of any of the operating condition such as normal applied load, sliding velocity, or duration of rubbing leads at some stage to a sudden change in the wear rate (weight loss per sliding distance). The simplest categories of wear exhibiting at different wear rates are mild and severe wear. Mild wear marks a smooth surface that often is smoother than the original surface, with minimum plastic deformation and oxide wear debris. CNT-Al nano-composite shows lower wear rate than pure aluminium and wear rate of all the tested materials increases with increasing normal applied load. Wear rate decreases with increasing CNT content from 0-1.5 wt% and increase slightly from 1.5-2 wt%, then increase rapidly after this range of CNT content. A distinctive abrasive and adhesive type of wear were observed from the morphological image of the worn surface.